The First Linac-based Stereotactic Body Radiation Therapy (SBRT) in Iran: A Case Study - Azma, Zohreh; Ameri, Ahmad; Rahnama, Nazanin; Mousavizadeh, Ahmad (Reports of Radiotherapy and Oncology, 2019)
Introduction: In this paper, we present the first experience of linac-based stereotactic body radiation therapy (SBRT) in Iran to treat a single liver metastasis. Case Presentation: A 23-year-old girl with a history of visceral melanoma of the uterine was treated for liver metastasis. Stereotactic body radiotherapy was selected as the treatment of choice after tumor recurrence following surgical removal and radiofrequency ablation. The treatment was delivered in five fractions to a total dose of 50 Gy. The patient tolerated the treatment without any considerable side effect and the lesion remained progression-free twelve months after treatment. Conclusions: It can be presumed that SBRT can be safely applied using IGRT-equipped conventional linear accelerators with a few but no adverse events if it is delivered with due consideration.